Produtividade e qualidade dos frutos de dez variedades de goiaba, em Visconde do Rio Branco, Minas Gerais, visando ao consumo ao natural e à industrialização - Rezende Pinheiro, Rubens Vicente; Marteleto, Luiz Otávio; Gomes de Souza, Antônio Carlos; Dias Casali, Vicente Wagner; Reis Condé, Alcides (Revista Ceres, 2025)
The perfomances-of 10 guava varieties were studied through evaluations of the following aspects: fruit weight produced per hectare; average fruit weight; pulp-seedpit ratio, based on weight and thickness of pulp; total titrable acids; Brix; total vitamin C and pectin content; dry matter; and, as to fitness for processing as adjudged by the preparation of the main types of processed products, such as: guava paste (known as «goiabada»), jelly, and stewed fruits in heavy syrup. The experiment was started in 1974, when the following varieties were planted: ‘Sao José Periforme’, ‘Tetraploide de Limeira’, ‘Brune Branca’, ‘Pirassununga Branca’, ‘Riverside Vermelha’, TAC+4’, ‘Pirassununga Vermelha’, ‘Brune Vermelha’, ‘Indus- trial de Montes Claros’, and ‘Péra’. This study of these varieties was conducted for three years, from August, 1977 through July, 1980. The physical and chemical parameters were determined during three harvest seasons. The tests for processing were made at the peak of harvest for each variety.